Dose enhancement of nanogold for prostate radiation: Monte Carlo simulation using the ICRP voxel computational male phantom - Wafa M. Al-Saleh; Turki Almatani (Journal of Taibah University for Science)
Using a male ICRP voxel computational phantom, Monte Carlo simulations were performed to estimate the dose enhancement ratio (DER) in prostate radiation for 6 and 10 MV photon energy. A fully validated linear accelerator head was used, initially with a single beam to calculate the DER for different concentrations of nanogold mixed with prostate tissue. Each energy was tested with (FF) and without (FFF) a flattening filter. The DER was then calculated for a verified 10 MV treatment plan to mimic the real treatment scenario. The results showed that the DER increased with concentration, especially for FFF mode. In addition, the flattening filter-free enhancement ratio (FFFER) was investigated, from which it was found that a 6 MV FFF with a 40 mg/ml concentration enhanced the dose by a factor of 1.03 compared to 6 MV FF. For the entire plan, the difference between FFF and FF for both energies was approximately 2%.